Primary Aldosteronism and Bone Metabolism: A Systematic Review and Meta-Analysis - Shi, Shaomin; Lu, Chunyan; Tian, Haoming; Ren, Yan; Chen, Tao (Frontiers in Endocrinology, 2020)
Background: Currently, increasing evidence shows that excess aldosterone may have an impact on bone health, and primary aldosteronism (PA) may be a secondary cause of osteoporosis. This problem is worthy of attention because secondary osteoporosis is always potentially reversible, which affects the selection of treatment for PA to some extent. The present systematic review will assess and summarize the available data regarding the relationship between PA and osteoporosis. Methods: Pubmed and Embase were searched for clinical trials related to the association between PA and bone metabolism. The results were limited to full-text articles published in English, without restrictions for the publication time. The quality of clinical trials was appraised and the data were extracted. Biochemical parameters of bone turnover in PA patients was assessed using random-effect meta-analysis. Descriptive analysis was performed for other parameters, for data is insufficient. Results: A final total of 15 articles were included in this review. The meta-analysis of 6 studies showed that subjects with PA had higher serum PTH levels (MD=21.50 pg/ml, 95% CI (15.63, 27.37), P<0.00001) and slightly increased urinary calcium levels (MD=1.65mmol/24h, 95% CI (1.24, 2.06), P<0.00001) than the EH controls. PA is associated with an increased risk of bone fracture. Bone loss in patients with PA may be reversed by MR antagonists or adrenal surgery. Conclusions: PA may be a secondary cause of osteoporosis and is associated with an increased risk of bone fracture. The clarification of the relationships between PA and bone metabolism requires additional prospective randomized controlled studies in a large sample. Keywords: primary aldosteronism, osteoporosis, bone metabolism, fracture, systematic review.